Global impact of gas flaring (2012)
This work deals with the multi-faceted impact of gas flaring on a global scale and the different approach employed by researchers to measure gas flared and its resulting emissions. It gives an overview of methods employed by these re-searchers in the oil and gas industry, academia and governments in attempt to determine ways of measuring and reducing gas flaring and its emission drastically. This approach so far includes analytical studies, numerical studies, modeling, computer simulations, etc. the goal behind each study being to mitigate the effects of gas flaring. The outcome indicates that there is a seemingly absence of a single global method, emission factor and estimation procedure used in the oil and gas industry all over the world to determine the volume of gas flared and its emissions be it from complete or incomplete combustion, sweet or sulphur present hydrocarbons and this poses a continuous problem in determining the actual impact of gas flaring and its emissions on human and its role in environmental degradation both at a local and global level. An attempt has also being made to cover up-to-date trends in gas flaring and current developments in some of the most flared countries.